Uma análise dos empreendedores e empreendimentos comerciais do centro da cidade de Mossoró-RN - França, Carlos Jorge Bezerra (Universidade Federal Rural do Semi-Árido, 2019)
The present work of conclusion of course has the purpose to analyze the entrepreneurs and commercial enterprises of the center of the city of Mossoró / RN. It is part of the project entitled "Mapping of entrepreneurship and profile of entrepreneurs of the municipalities of the state of Rio Grande do Norte", coordinated by Professor Maristélio da Cruz Costa, who is analyzing the possibilities of employment and income generation in all state of Rio Grande do Norte. This research places light on the points to be improved and on the qualities of entrepreneurs and entrepreneurs, such as: the most common gender among the entrepreneurs in the area studied, their age group, the predominant level of education, if there are and what are the means of entrepreneurs use and how companies are taxed. The survey also sheds light on how companies use, when they use it, technology to aid and improve their processes. Being that 35% of the businessmen of the researched area of the center of Mossoró do not use any type of technological means in their companies, making it impossible, in many cases, to maintain their products or services competitive. This research highlights the difficulties that entrepreneurs say they have to deal with in their ventures, the main one being the economic crisis, followed by high taxes and competition.
Monografia
Keywords: Empreendedorismo; Comércio; Serviço; Mossoró/RN; Economia; Entrepreneurship; Commerce; Service; Mossoró/RN; Economy; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA